Leveraging Digital Literacy for Student Advancement in Elementary Education: From Access to Empowerment - Rizky Amelia; Yogi Prihandoko (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2024)
In the modern educational landscape, the integration of digital technology into the lives of elementary school students is both inevitable and increasingly influential. However, the effective use of such technology hinges on a strong foundation in digital literacy, which equips students to navigate digital environments responsibly and productively. This study examines the pivotal role digital literacy plays in supporting the multidimensional development of primary school learners through a systematic literature review. Sixteen articles published between 2017 and 2023 were analyzed, sourced from SINTA-accredited journals (levels 1–5) and international conference proceedings. The review reveals that digital literacy contributes significantly to various areas of student development, including moral discernment, analytical and creative thinking, fine and gross motor skills, early bilingual competencies, social collaboration, and emotional articulation. Moreover, the findings emphasize the critical role of adult involvement—particularly from teachers and parents—in mediating students' engagement with digital media. With proper guidance, technology can become a powerful tool for enhancing both academic and personal growth in elementary education settings.